Imperative of Emotional Actualization of Action as a Means of Conveying Evaluative Meaning (Linguostylistic Studies, 2019)
In some linguistic contexts, verb forms, except a primary function of a category, can perform secondary functions, which reveal their specific features in the context of the grammar of evaluation. Despite the importance of the issue, few attempts have been made to study it in modern linguistics.The goal of the article is to characterize particular types of the transposed use of imperative forms in modeling axiological content. The study seeks to identify the modeling mechanisms of evaluation, based on the use of imperative forms in action emotional actualization (model Грошей їй дай; model Отак і роби добро) and highlight aspectually the features of the figurative use of the imperative forms as devices of tropeistics. The model Грошей їй дай manifests the ironic interpretation of one’s duties or somebody’s requirement to perform it which is expressed by the using imperative form, conveying negative speaker’s attitude to the person who motivates or encourages its performance, and to the action itself. There is no indication of the action doer in the constructions with the value of unwillingness and the pejorative attitude concerns the verbalized action. The grammatical igrem simulates the transposing use of the form: the speaker "tries on” himself an imperative form with an indicative tinge of obligation / compulsion, which causes a negative assessment.The imperative form in the model Отак і роби добро contains an indicative shade of meaning associated with an already accomplished or hypothetical action that appears inappropriate in view of other events. The speaker ironically «tries on» on himself an «impulse» to perform the action and evaluates it negatively. Grammatical igrem is modeling the transposed form of imperative used in the indicative meaning. Unlike the model Грошей їй дай, there is no semantic meaning of duty or compulsion. The intention to perform the action comes from the speaker. The action is evaluated negatively as inappropriate because of certain circumstances.
Keywords: axiological meanings; imperative models; ironing self-doing; Ukrainian language